CD20 positive CD8 T cells are a unique and transcriptionally-distinct subset of T cells with distinct transmigration properties - Martijn Vlaming; Vrouyr Bilemjian; Jimena Álvarez Freile; Harm Jan Lourens; Nienke van Rooij; Gerwin Huls; Tom van Meerten; Marco de Bruyn; Edwin Bremer (Scientific Reports, 2021)
Abstract The presence of T cells that are dimly positive for the B cell marker CD20 is well-established in autoimmunity and correlates with disease severity in various diseases. Further, we previously identified that the level of CD20-positive T cells was three–fourfold elevated in ascites fluid of ovarian carcinoma patients, together suggesting a role in both autoimmunity and cancer. In this respect, treatment of autoimmune patients with the CD20-targeting antibody Rituximab has also been shown to target and deplete CD20-positive T cells, previously identified as IFN-gamma producing, low proliferative, CD8 cytotoxic T cells with an effector memory (EM) differentiation state. However, the exact phenotype and relevance of CD20-positive T cells remains unclear. Here, we set out to identify the transcriptomic profile of CD20-positive T cells using RNA sequencing. Further, to gain insight into potential functional properties of CD20 expression in T cells, CD20 was ectopically expressed on healthy human T cells and phenotypic, functional, migratory and adhesive properties were determined in vitro and in vivo. Together, these assays revealed a reduced transmigration and an enhanced adhesive profile combined with an enhanced activation status for CD20-positive T cells.